Pengaruh kepemilikan institusional, komisaris independen, dan kompensasi rugi fiskal terhadap penghindaran pajak pada perusahaan manufaktur di BEI 2017 - 2019 - Muhammad Daniel; Eksa Ridwansyah; Arif Makhsun (Politeknik Negeri Lampung, 2022)
This study aims to determine the effect of institutional ownership, independent commissioners, and fiscal loss compensation. The hypothesis is H1 whether institutional ownership has an effect on tax avoidance, H2 whether independent commissioners have an effect on tax avoidance, H3 whether fiscal loss compensation has an effect on tax avoidance. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. Determination of the sample using the Purposive Sampling method, namely the selection with certain criteria and obtained 44 companies that meet the criteria, so the total number of samples is 123 company reports. The method of data collection is through secondary data documentation obtained from downloading financial reports published by www.idx.co.id. The technique used is using SPSS.V.22 test equipment and multiple linear regression test. The results of this study indicate that institutional ownership has no effect on tax avoidance, independent commissioners have no effect on tax avoidance, fiscal loss compensation has affect on tax avoidance and institutional ownership, independent commissioners, and fiscal loss compensation collectively affect tax avoidance.